Re-Sourceful Networks: Notes from a Mobile Social Networking Platform in India - Rangaswamy, Nimmi; Cutrell, Ed (Pacific Affairs, 2012)
The paper analyzes SMSGupShup, a mobile-centric social networking platform in India. It focuses on a set of dominant users (young, male) who are redefining the nature of micro-blogging and the creation of mobile networking communities. Like many social networking sites, assembling, maintaining and growing social networks are primary behaviours on GupShup. Unlike many others, where maintaining a personalized profile and conversing with a networked community take prominence, users of GupShup show markedly different messaging or broadcasting practices. While captivated by the idea of connecting with people all over India for the first time through the GupShup platform, the primary motivation of users is not conversation, forging a “second life” or building interest groups, but optimizing the networking service to expand one’s own group membership. From a qualitative study of user profiles, the paper demonstrates how GupShup can inform thinking about facets of mobile communities in developing countries: specifically, changing ideas about the networking platform as a “second social life” to one of a pecuniary “resource.”